A new species of Nanochromis (Teleostei: Cichlidae) from Lake Mai Ndombe, central Congo Basin, Democratic Republic of Congo - Schliewen, Ulrich K.; Stiassny, Melanie L.j. (Zootaxa, 2006)
Nanochromis wickleri, a new cichlid species from Lake Mai Ndombe in the central Congo basin, is described. The large, deep-bodied species differs from all congeners in the possession of an elevated soft dorsal fin ray count (10–11 vs. 5–8) and by the presence, in adults, of strongly produced membranous fin lappets on the second and third dorsal fin spines. Pending comprehensive phylogenetic analysis Nanochromis wickleri is tentatively placed within a morphologically diagnosable subclade of Nanochromis, herein named the “nudiceps group”.